1997
DOI: 10.1152/jn.1997.77.5.2360
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tuning to Sound Duration in the Inferior Colliculus of the Big Brown Bat, Eptesicus fuscus

Abstract: Neural tuning to different sound durations may be a useful filter for identification of certain sounds, especially those that are biologically important. The auditory midbrains of mammals and amphibians contain neurons that appear to be tuned to sound duration. In amphibians, neurons are tuned to durations of sound that are biologically important. The purpose of this study was to characterize responses of neurons in the inferior colliculus (IC) of the big brown bat, Eptesicus fuscus, to sounds of different dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
181
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 164 publications
(191 citation statements)
references
References 25 publications
(5 reference statements)
6
181
2
2
Order By: Relevance
“…One potential role for delayed excitation of the sort that could be provided by the DCN is the identification of sound duration. Neurons in the IC of both bats and mice can show tuning to the duration of the stimulus (Brand et al 2000;Ehrlich et al 1997), and this depends on an interaction between early inhibition and a delayed excitation in the IC (Faure et al 2003). The delays in excitation that can be provided by the long latencies of DCN pyramidal cells could also contribute to this circuit.…”
Section: Functional Role In the Auditory Systemmentioning
confidence: 99%
“…One potential role for delayed excitation of the sort that could be provided by the DCN is the identification of sound duration. Neurons in the IC of both bats and mice can show tuning to the duration of the stimulus (Brand et al 2000;Ehrlich et al 1997), and this depends on an interaction between early inhibition and a delayed excitation in the IC (Faure et al 2003). The delays in excitation that can be provided by the long latencies of DCN pyramidal cells could also contribute to this circuit.…”
Section: Functional Role In the Auditory Systemmentioning
confidence: 99%
“…It has been proposed that duration-selective neurons are present in early sensory areas for both auditory and visual information (Heron et al, 2012). Evidence for this claim comes from single cell recording studies in different mammals that have reported duration-selective neurons in both early auditory processing areas such as inferior colliculus and the auditory midbrain (Brand, Urban, & Grothe, 2000;Casseday, Ehrlich, & Covey, 1994;Ehrlich, Casseday, & Covey, 1997;He, Hashikawa, Ojima, & Kinouchi, 1997), as well as early visual areas such as area 17 & 18 (Duysens, Schaafsma, & Orban, 1996;Eriksson, Tompa, & Roland, 2008). One can argue that an early locus for duration processing can be beneficial given that the temporal integration window of neurons is known to increase along the visual processing hierarchy (Hasson, Yang, Vallines, Heeger, & Rubin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We would expect to find that different notes in the composition would be represented by different cells, just as in the spatial case. It is known already that cell in the inferior colliculus of the bat and ferret show time-interval tuning (Ehrlich et al 1997); if the HEC serves a global memory role we should expect temporal tuning there as well.…”
Section: ''Time'' Cellsmentioning
confidence: 95%
“…''Armreaching'' neurons in the parietal cortex of primates have been used to study how visual cues are transformed from eye coordinates to arm coordinates (Ferraina et al 1997). The inferior colliculus of the bat and ferret has been used as a model for time-interval coding (Ehrlich et al 1997). The hippocampal-entorhinal complex (HEC) and its neighboring regions, in particular, contain a rich array of cells tuned to kinematic variables.…”
Section: Introductionmentioning
confidence: 99%